2022
DOI: 10.1002/ptr.7641
|View full text |Cite
|
Sign up to set email alerts
|

Jatrorrhizine ameliorates Schwann cell myelination via inhibiting HDAC3 ability to recruit Atxn2l for regulating the NRG1‐ErbB2‐PI3K‐AKT pathway in diabetic peripheral neuropathy mice

Abstract: Diabetic peripheral neuropathy (DPN) is a chronic complication associated with nerve dysfunction and uncontrolled hyperglycemia. Unfortunately, due to its complicated etiology, there has been no successful therapy for DPN. Our research recently revealed that jatrorrhizine (JAT), one of the active constituents of Rhizoma Coptidis, remarkably ameliorated DPN. This work highlighted the potential mechanism through which JAT relieves DPN using db/db mice. The results indicated that JAT treatment significantly decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition, Gong et al. ( 2023 ) found that JAT offers more protection against DPN than other flavonoid alkaloids. After the treatment of JAT (50, 100 and 200 mg/kg) in db/db mice for eight consecutive weeks, it significantly improved the general physiological functions and nerve morphology.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Gong et al. ( 2023 ) found that JAT offers more protection against DPN than other flavonoid alkaloids. After the treatment of JAT (50, 100 and 200 mg/kg) in db/db mice for eight consecutive weeks, it significantly improved the general physiological functions and nerve morphology.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that epigenetics plays an important role in the pathogenesis of several diseases (Zhang, Guan, et al, 2020). Acetylation is an epigenetic modification commonly affected by histone acetyltransferases (HATs) and histone deacetylases (HDACs), of which histone deacetylase 4 (HDAC4) has been widely studied because it mediates the physiological and pathological processes of several acute and chronic kidney diseases (Gong et al, 2023; Liu et al, 2022). In diabetic nephropathy (DN), high glucose (HG) leads to nephrin deacetylation and ubiquitination by inducing HDAC4 expression, which in turn leads to podocyte damage and renal dysfunction (Tung et al, 2018).…”
Section: Introductionmentioning
confidence: 99%